DOT1L Activity Promotes Proliferation and Protects Cortical Neural Stem Cells from Activation of ATF4-DDIT3-Mediated ER Stress In Vitro. (29th September 2015) - Roidl, Deborah; Hellbach, Nicole; Bovio, Patrick P.; Villarreal, Alejandro; Heidrich, Stefanie; Nestel, Sigrun; Grüning, Björn A.; Boenisch, Ulrike; Vogel, Tanja
Abstract: Growing evidence suggests that the lysine methyltransferase DOT1L/KMT4 has important roles in proliferation, survival, and differentiation of stem cells in development and in disease. We investigated the function of DOT1L in neural stem cells (NSCs) of the cerebral cortex. The pharmacological inhibition and shRNA-mediated knockdown of DOT1L impaired proliferation and survival of NSCs. DOT1L inhibition specifically induced genes that are activated during the unfolded protein response (UPR) in the endoplasmic reticulum (ER). Chromatin-immunoprecipitation analyses revealed that two genes encoding for central molecules involved in the ER stress response, Atf4 and Ddit3 ( Chop ), are marked with H3K79 methylation. Interference with DOT1L activity resulted in transcriptional activation of both genes accompanied by decreased levels of H3K79 dimethylation. Although downstream effectors of the UPR, such as Ppp1r15a/Gadd34, Atf3, and Tnfrsf10b/Dr5 were also transcriptionally activated, this most likely occurred in response to increased ATF4 expression rather than as a direct consequence of altered H3K79 methylation. While stem cells are particularly vulnerable to stress, the UPR and ER stress have not been extensively studied in these cells yet. Since activation of the ER stress program is also implicated in directing stem cells into differentiation or to maintain a proliferative status, the UPR must be tightly regulated. Our and published data suggest that histone modifications, including H3K4me3, H3K14ac, and H3K79me2, are implicated in the control of transcriptional activation of ER stress genes. In this context, the loss of H3K79me2 at the Atf4- and Ddit3 -promoters appears to mark a point-of-no-return that activates the death program in NSCs.